Mediasi Penal Penyelesaian Perkara Pidana Pada Masyarakat Desa Tanjung Alai Kecamatan XIII Koto Kampar-Riau - Ferawati, Ferawati Ferawati; Dasrol, Dasrol Dasrol (Melayunesia Law, 2018)
One of the regions in Riau province that still applies customary law in resolving criminal cases is Tanjung Alai Kecamatan XIII Koto Kampar village which involves the role of ninik mamak as a mediator. The purpose of this research is to find out what crimes are resolved through customary law ( reasoning mediation) and how the process of resolving criminal acts trough the mechanism of customary law in the people of Tanjung Alai Kecamatan XIII Koto Kampar village. The results of this study  are expected to provide a solution for law enforcement officers in overcoming the large number of cases that cannot be resolved by the criminal justice subsystem and the problem of over capacity of existing prisons throughout Indonesia